2018
DOI: 10.1097/md.0000000000012580
|View full text |Cite
|
Sign up to set email alerts
|

Apelin

Abstract: Apelin, the ligand for the APJ receptor, is involved in the pathogenesis of atrial fibrillation (AF). However, whether serum apelin can predict the recurrence of AF after pulmonary vein isolation (PVI) has not been determined.A prospective cohort study was performed in patients with AF (but without structural heart disease) who were undergoing first-time PVI. Serum apelin-12 was measured by enzyme-linked immunosorbent assay. Echocardiographic examination was performed at baseline, 3 months, and 6 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…Встановлено, що рівень апеліну суттєво знижується вже на другу добу у пацієнтів з гострим інфарктом міокарда та у хворих на ішемічний інсульт. Слід зазначити, що рівень апеліну значно нижчий у курців в порівнянні з тими, хто немає цієї шкідливої звички [8,17,21] [3,14,20].…”
Section: вступunclassified
See 1 more Smart Citation
“…Встановлено, що рівень апеліну суттєво знижується вже на другу добу у пацієнтів з гострим інфарктом міокарда та у хворих на ішемічний інсульт. Слід зазначити, що рівень апеліну значно нижчий у курців в порівнянні з тими, хто немає цієї шкідливої звички [8,17,21] [3,14,20].…”
Section: вступunclassified
“…дослідження з певною долею ймовірності (відображено величиною отриманих ВШ) буде супроводжуватись зменшенням рівня апеліну-13 сироватки і навпаки -збільшення рівня пептиду сироватки буде призводити до зменшення величин ІЧ САТ, іЛП та середньої кількості ШЕ за 1 год. Це дозволяє думати про існування певних патофізіологічних зв'язків між рівнем апеліну-13, величинами АТ, ознаками перевантаження лівого передсердя, шлуночковою екстрасистолією та дисліпідемією, що ще раз доводить кардіопротекторний вплив апеліну-13 та знаходить підтвердження в ряді інших досліджень [3,5,11,15,20,22]. Позитивний LK з рівнем ЗХС свідчить про наявність прямого зв'язку між рівнем загального холестерину та рівнем апеліну-13 сироватки у хворих на ГХ ІІ стадії.…”
Section: обговоренняunclassified
“…However, peripheral blood apelin concentrations were not only significantly decreased in AF patients compared with healthy controls but also independently predicted recurrent AF in patients with persistent AF. This included cases occurring after pulmonary vein isolation in subjects without structural heart disease [170][171][172]. It has been suggested that low apelin levels may interfere with AF susceptibility through elevated atrial NADPH-dependent oxidative stress and the TGFβ/Smad2/α-SMA pathway associated with mitochondrial dysfunction and myocardial fibrosis [173,174].…”
Section: Apelinmentioning
confidence: 99%
“…For example, in a series of 93 patients with persistent AF who underwent cardioversion, individuals with lower levels of apelin at baseline had a higher rate of AF recurrence at the 6-month follow-up [ 67 ]. Another series of 61 patients with AF who underwent pulmonary vein isolation showed that patients with lower serum levels of apelin at baseline had a higher rate of AF recurrence at 6 months post-procedure [ 68 ]. Interestingly, comparing 200 obese women to 200 lean women, Zaki et al found that obese women had a higher level of serum apelin compared to their lean counterparts [ 69 ].…”
Section: Mechanisms Underlying Obesity-related Afmentioning
confidence: 99%